Acute flaccid paralysis laboratorial surveillance in a polio-free country: Brazil, 2005–2014 - Ivanildo P. Sousa; Fernanda M. Burlandy; Silas S. Oliveira; Amanda M. Nunes; Cristiane Sousa; Elaine M. da Silva; Jaqueline G. A. Souza; Valdemar A. de Paula; Ivone C. M. Oliveira; Fernando Neto Tavares; Eliane V. da Costa; Edson Elias da Silva (Human Vaccines & Immunotherapeutics, 2017)
The last case of paralytic poliomyelitis caused by wild poliovirus in Brazil occurred in 1989. The interruption of the indigenous poliovirus transmission was obtained through mass immunization campaigns to eligible children and an active epidemiological and laboratorial surveillance of all cases of acute flaccid paralysis (AFP) among children under 15 y of age. This paper describes and evaluates the performance of the AFP surveillance system in different geographic areas of Brazil between 2005 and 2014, using indicators recommended by WHO. AFP surveillance indicators as well as virological investigation of polio and non-polio enteroviruses in stool samples received in the laboratory were assessed from 2005–2014. During the period, 5463 cases of AFP were investigated. Of these, 55% were males and 45% were females. Those under 5 y of age represented 48% of all cases reported and investigated. AFP notification rate was within the acceptable values with mean value of 1.3 (North), 1.4 (Northeast), 1.1 (Southern), 1.0 (Southeast) and 1.4 (Midwest) cases of AFP per 100.000 population aged 15 y as well as the adequacy of fecal specimens received in the laboratory. Sabin- related polioviruses accounted for 1.7% of the isolates while, 6.7% were non-polio enterovirus with the values ranging from 5.0% to 8.9 %. No wild-type polio was found. The AFP epidemiological and laboratorial surveillance activities have been kept at appropriate levels in Brazil. These data are a very strong indication, which supports the status of country free of polio.